2013
DOI: 10.1002/jcp.24391
|View full text |Cite
|
Sign up to set email alerts
|

Altered bone development and turnover in transgenic mice over‐expressing Lipocalin‐2 in bone

Abstract: Lipocalin-2 (LCN2) is a protein largely expressed in many tissues, associated with different biological phenomena such as cellular differentiation, inflammation and cancer acting as a survival/apoptotic signal. We found that LCN2 was expressed during osteoblast differentiation and we generated transgenic (Tg) mice over-expressing LCN2 in bone. Tg mice were smaller and presented bone microarchitectural changes in both endochondral and intramembranous bones. In particular, Tg bones displayed a thinner layer of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 46 publications
6
50
0
Order By: Relevance
“…In the bone, LCN2 expression is detected in chondrocytes during embryonic development [38] and induced during osteoblast differentiation [31]. In this study, we observed that LCN2 is expressed in osteoclast lineage cells and that its expression is regulated during osteoclast development.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the bone, LCN2 expression is detected in chondrocytes during embryonic development [38] and induced during osteoblast differentiation [31]. In this study, we observed that LCN2 is expressed in osteoclast lineage cells and that its expression is regulated during osteoclast development.…”
Section: Discussionmentioning
confidence: 89%
“…Using transgenic mice that specifically overexpress LCN2 in osteoblasts, Costa et al reported that LCN2 negatively regulates bone development and formation by affecting growth plate development and attenuating osteoblast differentiation [31]. More recently, Rucci et al identified LCN2 as a novel osteoblast mechanoresponding gene that modulates bone homeostasis [39].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study by Costa et al indicated that osteoblasts in mice expressed LCN2. Moreover, their study suggested that LCN2 exerted both a negative effect on bone formation and a positive effect on bone resorption [8]. Another study supported the role of LCN2 in inducing bone loss [9].…”
Section: Introductionmentioning
confidence: 95%
“…Emerging evidence has revealed the association of LCN2 with bone. Costa et al found that transgenic mice over-expressing LCN2 in bone displayed bone micro-architectural changes and reduced bone mass, including a thinner layer of cortical bone and a decreased trabecular number [8]. LCN2 was also shown to reduce osteoblast differentiation and be involved in osteoblast-osteoclast coupling [8,9].…”
Section: Prace Oryginalnementioning
confidence: 99%